Perancangan Strategi Pengembangan Industri Tekstil dan Produk Tekstil di Kabupaten Tangerang Berbasis Kompetensi Inti - Saparudin Saparudin (Universitas Bunda Mulia, 2017)
This paper discusses the core competence of industry in Tangerang Regency using Analytical Hierarchy Process (AHP) and then performs strategy development, with Interpretive Structural Modeling (ISM) methods. The method used is a questionnaire to solicit opinions from experts and community members and conduct a series of expert discussions (Focus group discussion, FGD) to gets input for strategy development of core competence. From the data processing using the AHP, it was found that the core competence of Tangerang Regency is the textile industry and textile products. The core competence can be developed through three stages: early stage (the support of government policy, financial support, and infrastructure development), the main stage (engine restructuring and development of human resources), and the final stage (increasing productivity and strengthening of the industrial cluster).Keywords: Kompetensi Inti, Analytic Hierarchy Process, Interpretive Structural Modelling, Peta Rencana